(untitled) (Biological Sciences - PJSIR, 2025)
Five CMS lines viz. HO.1, Mehran, Thatta, PSF-025 and SH-3915 were crossed with three restorer male inbreds UC-666, Peshawr-93 and B-2 in a line x tester mating design. 15 F1 crosses were developed for genetic assessment. All eight characters including agronomic were studied in non-stress and water stress treatments. The genetic analysis indicated significant differences between treatments, inbred parents, F1 hybrids and parents versus hybrids for agronomic traits. Line x tester revealed the prominence of specific combing ability and involvement of dominant genes. The predominance of dominant genes were involved in advocating the traits considered because of higher ratio cr2D/cr2A and degree of dominance (cr2D/ cr2A) Yi) exceeded over unity in both the environments with few exceptions under stress condition. These results demonstrated the preponderance of dominant gene action, thus indicated the feasibility of hybrid sunflower developments. The variation due general combining ability GCA (cr2A) and specific combining ability SCA (cr2D) and degree of dominance (cr2D/ cr2A) Yi) being higher than unity for different traits indicated that cr2 SCA variances were far greater than cr2GCA indicating entire characters under study were predominantly advocated by dominant genes in both the environments. General combining ability of lines and testers indicated that lines, were good combiners for early maturity and seed yield were regarded as best general combiners, thus these inbreds may be crossed to produce prolific hybrids. Specific combining ability and heterotic estimates are essential genetic parameters presenting worth of F1 hybrid expansion. The hybrids like Thatta x UC-666, Mehran x Peshawar-93 and Ho.1 x B-2, on the basis of SCA effects were found as potential hybrids for earliness and seed yield traits in both the environments.